2000
DOI: 10.1007/s002689910099
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Survival of Transmural Advanced Gastric Carcinoma following Curative Resection: Multivariate Analysis of Prognostic Factors

Abstract: Patients with transmural (T2N0-T3N2) advanced gastric carcinoma comprise the largest group with uncertain outcome. These patients must be stratified according to the prognostic variables so the high risk group can be precisely identified. A total of 152 patients with transmural advanced gastric carcinomas were uniformly treated with a curative intent between 1979 and 1989 with at least a 7-year follow-up. Results and prognostic factors of long-term survival were analyzed by univariate and multivariate analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 23 publications
2
52
0
5
Order By: Relevance
“…Curative resection is an important prognostic factor for patients with advanced gastric cancer [19,20,21]. Although the prognosis of patients with tumors of Borr-mann type III and IV was poor in our current study because of a larger proportion of late stage and noncurative resection, those who underwent curative resections had better prognoses than those who underwent noncurative resection.…”
Section: Discussionmentioning
confidence: 47%
“…Curative resection is an important prognostic factor for patients with advanced gastric cancer [19,20,21]. Although the prognosis of patients with tumors of Borr-mann type III and IV was poor in our current study because of a larger proportion of late stage and noncurative resection, those who underwent curative resections had better prognoses than those who underwent noncurative resection.…”
Section: Discussionmentioning
confidence: 47%
“…In particular, for what concern gastric surgery, no studies were found in literature describing direct correlation between intra-operative blood losses and post-operative complications. Nevertheless, high blood losses [36,37] and subsequent transfusions [38] are anyhow associated with a higher rate of recurrence, especially peritoneal, and therefore poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance and optimal cutoff for predicting patients' outcomes as a function of EBL in GC remain controversial [15][16][17] . Inconsistency in the criteria for patient inclusion and analyses, combined with blood transfusion, are inextricably intertwined with EBL and are cited as a possible cause of the conflicting data.…”
Section: Discussionmentioning
confidence: 99%